Correcting Real Exchange Rate Misalignment : Conceptual and Practical Issues - Eden, Maya; Nguyen, Ha (World Bank, Washington, DC, 2012)
This paper studies the issue of real exchange rate misalignment and the difficulties in settling international real exchange rate disputes. The authors show theoretically that determining when a country should be sanctioned for real exchange rate "manipulations" is difficult: in some situations a country's real exchange rate targeting can be beneficial to other countries, while in others it is not. Regardless, it is difficult to establish whether a misaligned real exchange rate is intentionally manipulated rather than unintentionally caused by other policies or by various distortions in the economy. The paper continues by illustrating the difficulty in measuring real exchange rate misalignment, and provides a critical assessment of existing methodologies. It concludes by proposing a new method for measuring real exchange rate misalignment based on differences in marginal products between producers of tradable and non-tradable goods.